2019
DOI: 10.11646/zootaxa.4623.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Micromalthus debilis LeConte, 1878 (Coleoptera: Micromalthidae), an American wood-boring beetle new to Italy

Abstract: Micromalthus debilis LeConte, 1878, an alien wood-boring beetle, is recorded for the first time in Italy and is recognized as a pest on wood structures of historical buildings in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Every year new exotic beetles are intercepted in the main arrival points; however, these likely constitute only a limited fraction of the actual arrivals. It is interesting to note that most of the exotic species recently found in Italy have been captured in the natural environment already, and they probably have stable populations (Clark et al 2014;Zappi 2014;Salvato & Uliana 2016;Toma et al 2017;Guariento et al 2019;Mola & Yoshida 2019;Forbicioni 2019;Ruzzier & Colla 2019). The presence of Archophileuru spinosus in Apulia, although totally unexpected, is perfectly in line with the aforementioned records: beetles that usually escape the main control procedures or that are not targeted by the most-used monitoring systems.…”
Section: Discussionsupporting
confidence: 69%
“…Every year new exotic beetles are intercepted in the main arrival points; however, these likely constitute only a limited fraction of the actual arrivals. It is interesting to note that most of the exotic species recently found in Italy have been captured in the natural environment already, and they probably have stable populations (Clark et al 2014;Zappi 2014;Salvato & Uliana 2016;Toma et al 2017;Guariento et al 2019;Mola & Yoshida 2019;Forbicioni 2019;Ruzzier & Colla 2019). The presence of Archophileuru spinosus in Apulia, although totally unexpected, is perfectly in line with the aforementioned records: beetles that usually escape the main control procedures or that are not targeted by the most-used monitoring systems.…”
Section: Discussionsupporting
confidence: 69%
“…Amongst European countries, Italy has one of the highest numbers of intercepted, adventive and established non-native Coleoptera (e.g. Beenen and Roques 2010 , Denux and Zagatti 2010 , Kirkendall and Faccoli 2010 , Roy and Migeon 2010 , Sauvard et al 2010 , Yus-Ramos et al 2014 , Nardi et al 2015 , Montagna et al 2016 , Forbicioni 2019 , Ruzzier and Colla 2019 , Ruzzier et al 2020b , Ruzzier et al 2020a , Rattu et al 2021 , Ruzzier et al 2021c , Ruzzier et al 2022b , Ruzzier et al 2023a , Ruzzier et al 2023c ) and this condition is plausibly attributable to Italy's central role in international trade as a crossroads to and from Europe ( Roques 2010 , Rassati et al 2014 ). Given this latter condition, which sees Italy as a possible "gateway to Europe" for non-native species, it is essential to share distribution data to promote an ever-increasing level of attention both in Italy and neighbouring countries against possible natural spreading and introductions.…”
Section: Introductionmentioning
confidence: 99%
“…The yellow‐spotted longhorn beetle Psacothea hilaris hilaris (Pascoe, 1858) (Coleoptera, Cerambycidae, Lamiinae) represents one of the multiple cases of exotic wood boring beetles introduced into the Mediterranean Basin during recent decades (Cocquempot & Lindelöw, 2010; Eyre & Haack, 2017; Jucker et al, 2006; Marchioro et al, 2022; Ruzzier et al, 2022; Ruzzier & Colla, 2019; Ruzzier, Morin, et al, 2020). Rassati et al (2016) reported 34 exotic species detected in this area, belonging to Buprestidae (1 species), Cerambycidae (14 species) and individuals in 2 subfamilies of Curculionidae, Scolytinae (18 species) and Platypodinae (1 species).…”
Section: Introductionmentioning
confidence: 99%